Remote teaching technology in the fi eld of Olympic education of students - Иван Круглик; Юрий Курамшин (National University of Physical Education and Sport of Ukraine, 2017)
The article substantiates the distant pedagogical technology in the field of Olympic education and prove the effectiveness of its application on the basis of competence improvement, knowledge system development and introduction of students to the ideals and values of Olympism. Keywords: olympic education, remote pedagogical technology students.